2007
DOI: 10.1172/jci32377
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I polymorphisms are associated with development of infectious mononucleosis upon primary EBV infection

Abstract: Infectious mononucleosis (IM) is an immunopathological disease caused by EBV that occurs in young adultsand is a risk factor for Hodgkin lymphoma (HL). An association between EBV-positive HL and genetic markers in the HLA class I locus has been identified, indicating that genetic differences in the HLA class I locus may alter disease phenotypes associated with EBV infection. To further determine whether HLA class I alleles may affect development of EBV-associated diseases, we analyzed 2 microsatellite markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 31 publications
3
70
2
3
Order By: Relevance
“…In the current study, McAulay et al found that these same alleles were significantly more frequent in IM patients than in asymptomatic EBV-seropositive or EBV-seronegative individuals. The individuals with IM and possessing these associated HLA alleles also had lower lymphocyte but higher neutrophil counts, higher EBV loads, and milder IM symptoms than individuals not carrying these alleles (11).…”
Section: Genetic Predisposition To Immentioning
confidence: 93%
See 1 more Smart Citation
“…In the current study, McAulay et al found that these same alleles were significantly more frequent in IM patients than in asymptomatic EBV-seropositive or EBV-seronegative individuals. The individuals with IM and possessing these associated HLA alleles also had lower lymphocyte but higher neutrophil counts, higher EBV loads, and milder IM symptoms than individuals not carrying these alleles (11).…”
Section: Genetic Predisposition To Immentioning
confidence: 93%
“…In this issue of the JCI, McAulay and colleagues examine the relationship between natural variation in genetic markers in the HLA class I locus, which influences many aspects of the immune response, and the frequency of IM (11). Previous reports had demonstrated an association between certain HLA class I alleles and EBV-positive HL (12,13).…”
Section: Genetic Predisposition To Immentioning
confidence: 99%
“…Microsatellite markers in or near the HLA-A locus have been associated with a higher risk of IM after primary EBV infection. 28 HLA-A*02 is also associated with a lower risk for EBV-related Hodgkin lymphoma, while A*01 is associated with an increased risk for Hodgkin lymphoma. Analysis of the four-digit level HLA typing showed that the most common suballele, A*0201, was driving the protective effect.…”
Section: Epstein-barr Virus and Multiple Sclerosis Vs Hla E Sundqvistmentioning
confidence: 97%
“…The risk increase follows an incubation period-like distribution and is of a transient nature (20,21), suggesting that events related to control of primary EBV infection have an important impact on disease risk. However, propensity to develop IM has been associated with the HLA class I polymorphisms that were originally linked with EBVrelated HL, thus raising the possibility that the association between EBV-related HL and prior IM simply reflects shared genetic susceptibility (22).…”
mentioning
confidence: 99%